A LRT Control Method Using Sensor Information in Distribution Systems with a Large Amount of PVs and EVs. Issue 4 (March 2017) - NOSE, YOTARO; TSUJI, TAKAO; OYAMA, TSUTOMU; ITO, TAKAHARU; ABE, KATSUYA; MINAMI, MASAHIRO; ISHIBASHI, KAZUNARI
SUMMARY: It is of prime importance to maintain voltage profile within the proper range in distribution systems with a large amount of photovoltaics and electric vehicles (EVs). In particular, there is a possibility that line drop compensation (LDC) logic, which is utilized for the control of load ratio tap transformer (LRT) does not work properly when reverse power flow is included partially. Hence, in this paper, we have developed a new LRT control method based on the sensor information supposing that some section switchgears with sensors are introduced in the future distribution systems. Specifically, the extreme value of voltage profile is estimated by convergence calculation in the section between the section switchgear with sensor and LRT. Moreover, the voltage at the end node can be estimated by LDC method using sensor information of section switchgear. The proposed method was tested using a distribution system model and its effectiveness was shown.